Analysis of the effect of hydrodynamics over the activity and selectivity of the oxidative dehydrogenation of propane process in a packed bed reactor through CFD techniques. (15th November 2020) - Reyes-Antonio, Claudio Antonio; Cordero, Mario E.; Pérez-Pastenes, Hugo; Uribe, Sebastián; Al-Dahhan, Muthanna
Abstract: A study of the effect of hydrodynamics on the activity and selectivity of the oxidative dehydrogenation of propane (ODHP) of a non-isothermal Packed Bed Reactor (PBR) was implemented. 2D and 3D CFD models were employed, considering the mass, energy and momentum transport, and a 5-step oxidation Eley-Rideal kinetic model. The effect of the inclusion of porosity function was also carried out in order to capture non-homogeneities in the radial void fraction distribution on the predictive quality. The CFD model was validated against experimental and theoretical data reported in the literature. The validated model was used to perform a parametric sweep in order to determine the process inlet temperature which maximizes the conversion, selectivity and yield. The CFD model that considers the multiphysics in the ODHP led to an increase from 30% to 33% and from 20% to 24% in the conversion and the selectivity, respectively, which represents an increase of 22% and 20% with respect to the plug flow model. The 3D model exhibited a higher activity and reactivity respect to the plug flow model, similar to that reported for the membrane reactor. This reveals that incorporating hydrodynamics in all coordinates, results similar to dose one reactant, which emphasize the low predictive quality by using the plug flow model.